Circular Ribonucleic Acid circFTO Promotes Angiogenesis and Impairs Blood–Retinal Barrier Via Targeting the miR-128-3p/Thioredoxin Interacting Protein Axis in Diabetic Retinopathy - Guo, Jianjin; Xiao, Feng; Ren, Wei; Zhu, Yikun; Du, Qiujing; Li, Qian; Li, Xing (Frontiers in Molecular Biosciences, 2021)
Background: Increasing attention has been attracted to the role of circular RNAs (circRNAs) in ocular diseases. Previous study revealed that circ_0005941 (also known as circFTO, alpha-ketoglutarate dependent dioxygenase) was upregulated in the vitreous humour of diabetic retinopathy (DR), while its underlying mechanism in DR remains unknown. Methods: Retinal vascular endothelial cells (RVECs) treated with high glucose (HG) were used to establish the DR cell model. The in vivo assays were conducted using streptozotocin-induced diabetic mice. The circular structure and stability of circFTO was identified by Sanger sequencing and RNase R treatment. RT-qPCR analysis was used to detect the RNA expression. The levels of mRNA encoded protein thioredoxin interacting protein (TXNIP) or angiogenesis-associated proteins (VEGFA, PDGF and ANG2) and blood-retinal barrier (BRB)-related proteins (ZO-1, Occludin and Claudin-5) were measured using western blot. The viability of RVECs was measured by CCK-8 assays. The angiogenesis of RVEC was assessed by tube formation assays in vitro. Endothelial permeability assays were conducted to examine the function of BRB. The binding between genes was explored by RNA pulldown and luciferase reporter assays. Results: CircFTO was upregulated in HG-treated RVECs. CircFTO deficiency reversed HG-induced increase in the viability and angiogenesis of RVECs and alleviated HG-mediated impairment of BRB. MiR-128-3p bound with circFTO and was downregulated in HG-treated RVECs. TXNIP was a downstream target gene of miR-128-3p. TXNIP was highly expressed in DR cell model. Rescue assays revealed that circFTO promoted angiogenesis and impaired blood retina barrier by upregulating TXNIP. In the DR mouse model, circFTO silencing inhibited angiogenesis and promoted BRB recovery in vivo. Conclusion: CircFTO promotes angiogenesis and impairs blood retina barrier in vitro and in vivo by binding with miR-128-3p to upregulate TXNIP in DR.